Hypoplastic Breast Anomalies in the Female Adolescent Breast - Winocour, Sebastian; Lemaine, Valerie (Seminars in Plastic Surgery, 2013)
Hypoplastic breast anomalies remain a reconstructive challenge. In this article, the authors review the spectrum of nonsyndromic breast hypoplasia in the adolescent girl, namely idiopathic breast hypoplasia and tuberous breast deformity. Challenges specific to this population include (1) identifying the ideal timing for surgery, (2) choosing the optimal reconstructive method while taking into consideration ongoing changes in the female body (e.g., future pregnancy), and (3) considering the use of a two-stage reconstructive approach to gradually expand the skin envelope. A comprehensive review of surgical techniques that address these conditions is provided, taking into account the evolution and the most recent advances in surgical techniques.
Keywords: breast hypoplasia; tuberous breast; adolescent